Effects of Task Oriented Exercises with Altered Sensory Input on Balance and Functional Mobility in Chronic Stroke: A Pilot Randomized Controlled Trial (Bangladesh Journal of Medical Science, 2017)
Background: Stroke subjects presented with greater postural instability which lead to challenge their balance control in sensory conflict conditions. Studies have shown that deficits of sensorimotor integration and an inability to select the appropriate sensory input are associated with balance measures following stroke.However, limited studies have been focused to sensorimotor integration in balance rehabilitation.Objective: Our study aimed to evaluate the Task Oriented Training (TOT) with sensory manipulation to enhance balance and functional mobility in chronic stroke subjects.Design: Randomized controlled pilot study.Setting: Department of Physiotherapy in a Tertiary care Hospital.Subjects: A convenience sample consisting of 26 hemi paretic subjects at least 6 months post stroke duration with Brunnstroms recovery stage ?5 for the lower limb and Berg Balance Score of 40 or above were randomly assigned control group (n=13) and in experimental group (n=13).Interventions: Control group received the conventional physical therapy and in the Experimental group received TOT with manipulations of sensory inputs and provision of sensory conflict for the trunk and lower limb focusing on balance and mobility were implemented for 15 sessions, 5 days a week for 3 weeks with each session of 45-60 mints duration.Outcome measures: Dynamic Gait Index (DGI), Timed Up and Go Test (TUGT) and Fall Efficacy Scale (FES) were analyzed before and after the training.Results: Post training there was a significant improvement in all the outcome measurements for both the groups. However components 3, 4 and 5 of DGI, TUGT and FES of experimental group had a highly significant statistical difference between-group analysis with p